LEADERSHIP INTELLIGENCE: CONTENT AND STRUCTURE IN THE CONDITIONS OF INDUSTRY 4.0 - MEREZHKO, Volodymyr; KORZH, Nataliia (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article states that most organizations today recognize the fact that smart leadership contributes to overall organizational effectiveness and change. After all, such leaders not only have skills and knowledge accumulated through experience, but are also able to manage (maneuver) them in order to effectively achieve goals and implement changes. The article emphasizes that the globalized and unpredictable environment requires the formation of a new level of leadership intelligence. The purpose of this article is to form the content of leadership intelligence, which is designed to realize the possibilities of Industry 4.0. In addition, it is important to justify its components, the integration of which will provide various mechanisms contributing to a better understanding and interpretation of behavior and events in organizations. The key to the success of leadership intelligence of the highest level should be the managers’ awareness of the need to form their own emotional stability, ensuring cognitive balance and taking into account local cultural models and spiritual norms. We also noted that a leader must have cognitive skills, business skills, interpersonal skills, and strategic skills. In addition, he should be characterized by openness and transparency, emotional honesty, social perception, employee orientation, a culture of mistakes, the ability to think broadly, quickly and critically, understand the unique requirements of the environment and see the opportunities of today. The structure of leadership intelligence, which consists of the elements of launching an anti-stress mechanism aimed at development, change and humanity, is substantiated. Such components are the coefficient of intelligence, emotional, cultural and spiritual coefficients.